Developing web-based mathematics learning media for statistical material - Yuwono, Timbul; Ramadan, Syahrul; Fayeldi, Trija; Wahyuni, Tri (Jurnal Pendidikan Matematika RAFA, 2023)
This research aimed to describe the validity, practicality and effectiveness of web-based learning media. The subject of this research was the students of 9th grade of MTs Al Muslihuun Sumbermanjing Wetan. Validation result of this research from the media validation was 3,70 included into very valid category and the result of material’s validation was 3,67 that mean very valid category. The result of students’ response was obtained 3,39 from small group trials and 3,50 for large group trials, that mean that the media got very practical category and the result of the students’ test is 88,9% from small group trials and 82,6% from large group trials that showed the percentages of students achieve the minimum completeness criteria score. Therefore, the web-based learning media was stated as valid, practical and effetive and could be used in the mathematics learning process.